Scalability, test–retest reliability and validity of the Brief INSPIRE-O measure of personal recovery in psychiatric services - Moeller, Stine Bjerrum; Larsen, Pia Veldt; Austin, Stephen; Slade, Mike; Arendt, Ida-Marie T. P.; Andersen, Martin Stolpe; Simonsen, Sebastian (Frontiers in Psychiatry, 2024)
Introduction. Mental health services have transitioned from primarily treating symptoms towards emphasizing personal recovery. Despite its importance, integrating personal recovery into clinical practice remains a work in progress. This study evaluates the psychometric qualities of the Brief INSPIRE-O, a five-item patient-reported outcome measure assessing personal recovery. Method. The study collected data from 2018-2020 at the Mental Health Services, Capital Region of Denmark, utilizing an internet-based system examining 8192 non-psychotic patients receiving out-patient treatment. Materials. The study evaluated the Brief INSPIRE-O and used measures of symptomatology (SCL-10), well-being (WHO-5) and social functioning (modified SDS). Results. The study population comprised 76.8% females, a mean age of 32.9 years, and diagnoses included anxiety (28%), depression (34%) and personality disorder (19%). The Brief INSPIRE-O mean score (39.9) was lower than the general population norm (71.1). Brief INSPIRE-O showed acceptable test-retest reliability (0.75), scalability (0.39) and internal consistency (0.73). Correlations with other mental health criteria were in the expected direction for symptomatology (-0.46), well-being (0.60) and social functioning (-0.43) and remained consistent across diagnoses. Discussion. The Brief INSPIRE-O demonstrated strong psychometric qualities and could be recommended as a measure of personal recovery for use in both research and clinical practice. Its strong theoretical basis and short completion time makes it suited for use in research. Incorporating Brief INSPIRE-O into clinical assessment will further support the further process of mental health systems re-orientating towards personal recovery.